MORNING MOOD BOOSTERS: WAYS TO INCREASE STUDENTS EFFECTIVENESS AT SCHOOL - Dwiaryanti, Risca (Jurnal Kajian Pendidikan dan Psikologi, 2025)
This article analyze students bad mood in the morning because of some problems, such as; (1) Lack of Sleep, (2) Morning Rush, (3) Unpreparedness: (4) Social Pressure (5) Hormonal Changes (6) Breakfast Struggle: (7) Stress and Overwhelm (8) Transportation Issues (9) Physical Discomfort (10) Lack of Motivation. Those problems make them get bad mood to go to school.  The aim of this writing may help students, teachers, and parents aware of morning motivation to start the day to face a long journey in a day and get some good achievement at the end of the day. Method used in this article is literature review. The writer find some related articles in online journals, analyze and give some solution. In conclusion, to prepare children ready to go school, there must be some mood booster. These can make them feel comfortable and get new spirit, so that they easy to get high achievement at school.